1993
DOI: 10.2172/140430
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of severe accident risks: Methodology for the containment, source term, consequence, and risk integration analyses; Volume 1, Revision 1

Abstract: Availability uf Reference Materials C i t r d In NRC PublicationsMost documents clted In NRC pubkatlons will be avallable from one of the following sources: Single coples of NRC draft reports are available free, to the extent of supply, upon written request to the Office of lnformatlon Resources Management, Dlstrlbutlon Sectlon. U S . Nuclear Rogulatory Commlsslon, Washlngton, DC 20555-0001.Coples of Industry codes and standards used In a substantive manner In the NRC regulatory process are malntalned at the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This method has the drawback of often being very expensive to apply, but it is one of the most straightforward and therefore economical to implement, and all statistical evaluation methods may be rigorously used on the resulting sample space [Devictor 2005]. It will also correctly account for any discontinuities and transitions between physical regimes, can incorporate correlations between input parameters, and works well for input parameters with large uncertainty ranges [Gorham 1993].…”
Section: Monte Carlo Methodsmentioning
confidence: 99%
“…This method has the drawback of often being very expensive to apply, but it is one of the most straightforward and therefore economical to implement, and all statistical evaluation methods may be rigorously used on the resulting sample space [Devictor 2005]. It will also correctly account for any discontinuities and transitions between physical regimes, can incorporate correlations between input parameters, and works well for input parameters with large uncertainty ranges [Gorham 1993].…”
Section: Monte Carlo Methodsmentioning
confidence: 99%
“…SNL is the lead laboratory in the development of the PRA methods at nuclear power plants. In the NUREG/CR-4551 document series (Gorham et al, 1993), SNL reported an integrated analysis of four accident phases for an overall expression of risk for the U.S. Nuclear Regulatory Commission (NRC). Key references for PRA tools also include NUREG/CR-2300 (1983) and NUREG/ CR-6823 (2003).…”
Section: Probabilistic Risk Assessment Toolsmentioning
confidence: 99%
“…Accident progression analysis investigates the core damage process both in and outside the reactor vessel and the resultant impact on the containment. Source term analysis estimates the radionuclide release associated with the accident conditions, and consequence analysis calculates the offsite consequences in terms of health effects and financial loss (Gorham et al, 1993).…”
Section: Probabilistic Risk Assessment Toolsmentioning
confidence: 99%
See 1 more Smart Citation